2013
DOI: 10.4038/sljog.v35i2.6167
|View full text |Cite
|
Sign up to set email alerts
|

Role of indomethacin in polyhydramnios

Abstract: Objective: To observe the role of indomethacin in polyhydramnios.Method: This was a prospective, longitudinal and analytical study conducted in Kathmandu University Hospital, Dhulikhel from 1st July 2011 to 1st of December 2012. There were 32 patients included in the study. Indomethacin was administered orally at the dose of 25 mg three times a day for 1 week. The patients were admitted for observation of clinical symptoms, fundal height, fetal status and amniotic fluid index measurement. After the delivery, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 19 publications
3
0
0
Order By: Relevance
“…Mean gestational age at presentation in our study was 30.78±1.56 weeks similar to study by Abhyankar et al and Carmona F et al 16,17 In our study there was a significant decrease in amniotic fluid when given in patients with Idiopathic Polyhydramnios similar to study conducted by Abhyankar et al, Abou-GhannamG et al and Block Abraham Dana et al 16,18,19 Pregnancy was prolonged by an average of 5.5±1.89 weeks and average duration of therapy was 22.5±6.38 days. These findings were similar to study conducted by Shrestha A et al and Abhyankar et al 11,16 Kirshon et al and Mamopoulos et al reported that reduction in amniotic fluid was not detrimental to the fetus and on discontinuation amniotic fluid returned to normal. 20,21 But in our study one patient who continued taking Indomethacin, at home, without any follow up and surveillance returned with severe oligohydramnios.…”
Section: 04supporting
confidence: 90%
See 2 more Smart Citations
“…Mean gestational age at presentation in our study was 30.78±1.56 weeks similar to study by Abhyankar et al and Carmona F et al 16,17 In our study there was a significant decrease in amniotic fluid when given in patients with Idiopathic Polyhydramnios similar to study conducted by Abhyankar et al, Abou-GhannamG et al and Block Abraham Dana et al 16,18,19 Pregnancy was prolonged by an average of 5.5±1.89 weeks and average duration of therapy was 22.5±6.38 days. These findings were similar to study conducted by Shrestha A et al and Abhyankar et al 11,16 Kirshon et al and Mamopoulos et al reported that reduction in amniotic fluid was not detrimental to the fetus and on discontinuation amniotic fluid returned to normal. 20,21 But in our study one patient who continued taking Indomethacin, at home, without any follow up and surveillance returned with severe oligohydramnios.…”
Section: 04supporting
confidence: 90%
“…8,9 The reported incidence of polyhydramnios varies between 0.4 and 3.3%. 4,10 In our study incidence observed was 1.47% which is similar to the study conducted by Shrestha A et al 11 In our study Idiopathic Polyhydramnios accounted for 70% of the cases which was similar to a study conducted by Pri-Paz et al and Sandlin AT et al 4,12 Wiegand SL et al reported that most of the cases (78%) belonged to mild polyhydramnios and about 21% of cases were moderate to severe polyhydramnios. 13 But in our study as 18 cases of Idiopathic Polyhydramnios with symptoms were included, 6 cases (33.33%) belonged to mild and 12 cases (66.66%) belonged to moderate to severe polyhydramnios.…”
Section: 04supporting
confidence: 89%
See 1 more Smart Citation